THE TECHNICAL MEANS OF EDUCATION IN THE MODERNIZING EDUCATIONAL SYSTEMS (EDUCATION IN THE 21ST CENTURY, 2023)
The educational means and the technical means of education in the current state of the civilization development have essentially promoted the educational process to become more interesting and effective.In the paper it is represented that throughout human history the corresponding educational systems have successfully used the special results of science and technology of the current period beginning from mechanical calculators – arithmometers, slide rule and ending with audiovisual means – film projector, tape player, video player and in the 21st century also computers, internet and other means of ICT. In that sense, the history of the society educational life can be divided into five periods, which are: illustrative visual, verbal, printed technical, audiovisual and informative.The rapid technological advancement, the strong and demanded entrance of the modern ICT means into the educational system has created a completely new state which is presented in the literature as a term of informatization of the education.In the 21st century the modernization of the education mostly depends on its level of informatization. In the modern world where the development and modernization of the educational systems depend on the level of social and economic power of the state it is noticed that there are certain differences in providing educational systems with modern ICT means and internet as well.  Nevertheless, the most powerful countries in the world are already entering into the stage of informative society, where the educational system is not only informatizated, but also is ready to immediately feel the need of usage of new technologies as educational technical means.The content of the article confirms the fact, that the technical means based on new technologies in educational process can perform all the functions of the similar means created during the history in a more effective, incomparably high quality and complex way.
Keywords: Technical means, computer technology, teaching means, teaching technology, modernization, information, information society